The impact of competition on the efficiency of the telecommunication s industry in Uganda - Kavuma, Bosco Kintu (Kampala, 2001)
Unpublished thesis (M.A., Econ.Pol.& Mgt.) - Makerere University, 20 01.
Includes bibliographical references (p. 81-83).
Keywords: telecommunication -- Uganda